Evaluation of a Colombian oregano oil (Lippia origanoides Kunth) and a novel yeast product from Pichia guilliermondii, alone or in combination, on rumen fermentation, methanogenesis and the microbiome in the rumen simulation technique - Ramos-Morales, Eva; Bolton, Emily; Lyons, Laura; Carreño, David; Jones, Eleanor; Mayorga, Olga; Ariza-Nieto, Claudia; Newbold, Charles James (Frontiers in Animal Science, 2022)
In this study, Lippia origanoides Kunth, native of the Alto Patía region in Southwest Colombia, and Pichia guilliermondii LV196, an inactivated yeast from the germplasm bank of Agrosavia (Colombian Agricultural Research Corporation), alone or combined, were tested for their long-term effect on rumen fermentation and methanogenesis whilst also characterising their effect on bacterial and methanogen communities. Whereas essential oils act through selective inhibition of microbial groups, yeasts are thought to work through the selective stimulation of key microbes in the rumen. We hypothesized that yeast supplementation could modulate the antimicrobial effect of a high thymol-containing oregano oil, allowing a more efficient feed utilization whilst decreasing methane production. When added to a rumen simulating fermentor (RUSITEC), Lippia origanoides Kunth at 132 microliters/d had a detrimental effect on rumen fermentation which was accompanied by a reduction in the relative abundance of protozoa and fungi and a profound impact on the bacterial and archaeal communities. Pichia guilliermondii LV196 at 0.5 g/L, however, had no effect on fermentation parameters or nutrient utilization, and neither changes in microbial abundances or in the structure of bacterial and archaeal communities were observed. Since Pichia guilliermondii LV196 did not stimulate microbial numbers nor activity, we could not test whether it could act as to counterbalance the antimicrobial effect of the essential oil. Future studies need to both investigate lower levels of essential oil addition, but also to re-examine the effects of P guillermondii in the rumen and/or to replace it with other yeast of known biological activity when combined with oils extracted from Lippia origanoides Kunth.